Adaptive Cruise Control based Motor Acceleration Control using Fuzzy Logic Methods - Putra Maulana Yusuf; Joko Hariyono; Joko Slamet Saputro; Agus Ramelan; Feri Adriyanto; Miftahul Anwar (Universitas Sebelas Maret (UNS), 2023)
The paper presents a method for adaptive cruise control based motor acceleration control. On the long-distance driving, using vehicles that have a risk for accidents. One of these accidents is collisions between vehicles in front of them which can cause multiple collisions. With the help of the ACC feature, it can reduce the occurrence of these accidents which are caused by the driver's fatigue and weather conditions on long-distance trips. By using the Fuzzy adaptive cruise control system, it is successful in adjusting the acceleration set on the fuzzy system, and with the help of the GUI it can make it easier for the operator to set the appropriate acceleration.